Comparing eating disorder treatment outcomes of transgender and nonbinary individuals with cisgender individuals. Issue 11 (23rd September 2022) - Riddle, Megan C.; Robertson, Lee; Blalock, Dan V.; Duffy, Alan; Le Grange, Daniel; Mehler, Philip S.; Rienecke, Renee D.; Joiner, Thomas
Abstract: Objective: The purpose of this study was to compare symptom severity of eating disorders (EDs), depression and anxiety at admission and discharge for transgender and nonbinary (TNB) individuals and cisgender adult individuals receiving treatment for EDs at higher levels of care (HLOC), adding to the limited research in this area. Method: Participants were 25 TNB individuals and 376 cisgender individuals admitted to a HLOC ED treatment facility. Participants completed the Eating Disorder Examination Questionnaire (EDE‐Q), Patient Health Questionnaire‐9, and Beck Anxiety Inventory at admission and discharge. Results: TNB individuals showed significant improvements on EDE‐Q global scores between admission and discharge (Cohen's d = 1.27), and showed similar improvements on the EDE‐Q over the course of treatment (Cohen's d = 0.06) when compared to cisgender individuals. TNB individuals had more severe depression at admission (Cohen's d = 0.61). Although depression improved over the course of treatment for both groups, TNB individuals showed less improvement (Cohen's d = 0.59). Suicidality was higher for TNB individuals on admission and discharge and did not improve significantly over the course of treatment (Cohen's d = 0.38). Discussion: This study provides preliminary evidence that TNB and cisgender individuals show similar improvement in ED symptoms during HLOC treatment. However, TNB individuals have more severe depression and less improvement in depression compared to cisgender individuals, without improvement in suicidality. TNB individuals may benefit from care targeting depression and suicidality during ED treatment. Public Significance Statement: TNB individuals have increased risk of EDs. Little research addresses how TNB individuals respond to ED treatment, which was traditionally created for cisgender individuals. We present one of the first studies examining ED treatment outcomes for TNB adults. TNB individuals showed improved ED symptoms with treatment, but less improvement in depression and their suicidality remained elevated. This suggests the need for targeted treatment.